1989
DOI: 10.7326/0003-4819-111-10-807
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Levels of a Parathyroid Hormone-like Protein in Malignancy-Associated Hypercalcemia

Abstract: The data indicate a relation between the serum concentration of iPLP and the presence of hypercalcemia in solid malignancies. The results support a role for PLP as a humoral mediator of hypercalcemia in most patients with solid tumors. Measurement of iPLP should be useful in the differential diagnosis of hypercalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
2
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(71 citation statements)
references
References 27 publications
4
63
2
2
Order By: Relevance
“…This nonsuppressible immunoreactivity may represent biologically inert NH2-terminal material or may represent a level of biologically active PTHRP whose hypercalcemic activity may be neutralized by compensatory mechanisms. An analogous situation has been reported in humans with tumors in which elevated circulating concentrations of PTHRP have been described in association with normocalcemia (19,37,38).…”
Section: Discussionmentioning
confidence: 78%
“…This nonsuppressible immunoreactivity may represent biologically inert NH2-terminal material or may represent a level of biologically active PTHRP whose hypercalcemic activity may be neutralized by compensatory mechanisms. An analogous situation has been reported in humans with tumors in which elevated circulating concentrations of PTHRP have been described in association with normocalcemia (19,37,38).…”
Section: Discussionmentioning
confidence: 78%
“…Our recent clinical studies on surgical and autopsy specimens obtained from patients presenting with HHM revealed a very close relationship between the production of PTHrP and the development of HHM, suggesting that PTHrP plays a key role in the pathogenesis of HHM (Honda et al, 1988a;Tsuchihashi et al, 1990). Further support for this conjecture comes from recent studies reporting significantly elevated plasma PTHrP levels in patients with HHM (Budayr et al, 1989a;Burtis et al, 1990). …”
mentioning
confidence: 80%
“…Since the bioactivities were measured at the bottom portion of the (Gkonos et al, 1984;Weir et al, 1988;Kukreja et al, 1988;Ikeda et al, 1988). However, Mehdizadeh et al (1989) (Honda et al, 1988a;Budayr et al, 1989a;Burtis et al, 1990;Tsuchihashi et al, 1990). Since none of these tumours developed metastases, it is reasonable to assume that the hypercalcaemia developed in tumour-bearing nude mice was induced by the production of hypercalcaemic factor(s) by tumour tissues, not by bone metastases.…”
Section: Bio-pthrp In Tumour Tissuesmentioning
confidence: 99%
“…On the other hand, there are reports suggesting that humeral hypercalcemia is mediated by a peptide that resembles PTH. 10,13,14 Hypercalcemia in hematological malignancies is often cytokine/growth factor mediated. 15 In conclusion, our patient represents a rare complication of an uncommon hematological malignancy and illustrates the fact that hypercalcemia is a serious complication of cancer.…”
Section: Discussionmentioning
confidence: 99%